Evaluation of a welfare assessment tool to examine practices for preventing, recognizing, and managing pain at companion-animal veterinary clinics - Dawson, Lauren C. (Can J Vet Res, 2017)
Successful prevention, recognition, and treatment of pain are integral to ensuring veterinary patient welfare. A canine and feline welfare assessment tool, incorporating verbal interviews with veterinarians using open-ended questions, was developed to assess pain management practices that safeguard and improve patient welfare. The tool was evaluated in 30 companion- and mixed-animal veterinary clinics in Ontario in order to assess its reliability, feasibility, and validity, while also benchmarking current practices. Responses were analyzed according to a scoring scheme developed based on published literature and expert opinion. Based on weighted kappa statistics, interview scoring had substantial inter-observer (K(w) = 0.83, 0.73) and near-perfect intra-observer (K(w) = 0.92) agreement, which suggests that the tool reliably collects information about pain management practices. Interviews were completed at all recruited clinics, which indicates high feasibility for the methods. Validity could not be assessed, as participants were reluctant to share information about analgesic administration from their clinical records. Descriptive results indicated areas for which many veterinarians are acting in accordance with best practices for pain management, such as pre-emptive and post-surgical analgesia for ovariohysterectomy patients, and post-surgical care instructions. Areas that offer opportunity for enhancement were also highlighted, e.g., training veterinary staff to recognize signs of pain and duration of analgesia in ovariohysterectomy patients after discharge. Overall, based on this limited sample, most veterinarians appear to be effectively managing their patients’ pain, although areas with opportunity for enhancement were also identified. Further research is needed to assess trends in a broader sample of participants.